Upaya Pengembangan Bakat Olahraga Siswa Di SMA Negeri 1 Babadan Ponorogo - Febbyananda Rigiddwi Radiant Putra; Fajar Ari Widiyatmoko (YLPK Mahardhika, 2022)
This research is motivated by the poor performance of extracurricular students at SMA Negeri 1 Babadan, this can be seen from the lack of achievement that has not been maximized and the lack of competition in Ponorogo as well as the lack of talented seeds that make it difficult to capture the talents of students who tend to train from the start. This research is a qualitative research and aims to find out the talent development efforts of students at SMA Negeri 1 Babadan. This research uses qualitative methods and the sources of data taken are primary and secondary. Primary data is data obtained in verbal form from informants, while secondary data is sourced from student achievement documents. The research subjects used as informants in the interviews were the principal, physical education teacher, 3 high achieving students and 4 underachieving students. In accordance with the object, this research is a field research or field research. Data collection was done by preparing interview instruments for each informant.